Prescription Drug Abuse Among Patients in Rural Dental Practices Reported by Members of the National Dental PBRN. Issue 2 (6th August 2019) - McCauley, Jenna L.; Nelson, Joni D.; Gilbert, Gregg H.; Gordan, Valeria; Durand, Scott H.; Mungia, Rahma; Meyerowitz, Cyril; Leite, Renata S.; Fillingim, Roger B.; Brady, Kathleen T.; ,
Abstract: Purpose: This study compared rural to nonrural dentists with respect to opioid prescribing practices, perceptions about prescription drug abuse among patients, and training relevant to pain management and addictions. Methods: A web‐based, cross‐sectional questionnaire was administered to practicing dentist members of the National Dental Practice‐Based Research Network (PBRN; N = 822) and linked with network enrollment questionnaire data regarding practitioner demographics and practice characteristics. Pain management prescribing practices and perceptions regarding relevance and scope of addiction and drug diversion among patients were assessed. Rural practice was defined as a practice whose ZIP Code has more than 50% of its population in either a nonmetropolitan county and/or a rural Census tract. Findings: Rural dentists were significantly more likely than their nonrural counterparts to recommend nonsteroidal anti‐inflammatory agents/acetaminophen in combination with prescribing an opioid [F (1, 820) = 4.59, P = .03]. Compared to nonrural dentists, rural dentists were more likely to report that opioid abuse/diversion was a problem in their practices [ χ 2 [1, n = 807] = 6.85, P < .001], were more likely to have suspected a patient of abuse or diversion [ χ 2 [1, n = 807] = 10.12, P = .001], and were more likely to have refrained from prescribing due to suspicions of abuse or diversion [ χ 2 [1, n = 807] = 12.49, P < .001]. Conclusion: Rural dentists may be disproportionately impacted by patients' opioid abuse and represent a viable target for educational outreach that encourages screening, identification, and referral of patients in need of drug abuse treatment.